Etnopolitiske utmaningar i historieformidling – Grunnforteljingar om samefolket i Noreg - Kvande, Lise (Noregs teknisk-naturvitskaplege universitet, Trondheim, 2015)
The article discusses the place and the status of the Sami people in historical narratives in Norway. It focuses on history as a school subject but this focus can only be understood by looking at changes in contexts. Of special interest here is the presentations of the Sami in Norwegian textbooks, the status of the Sami people in Norwegian society, and changes in the perspectives in historical research. History has played a significant role in the nation and state building processes in the Western countries, however in the last decades most European societies have seen immigration at a larger scale than before and, hence, new challenges concerning national identity and inclusion of new groups in the new histories of the nations. The indigenous people in Norway, the Sami, have lived both within and across the Norwegian borders. For centuries they were absent in the political and cultural narratives of Norway. After WW II they gradually achieved political recognition and legal rights but it was not until the 1970s they obtained space in Norwegian textbooks. The article shows how narratives about the Sami people have been presented and how they have changed in the last 40 years. The narratives first made the Sami visible, then they focused on the Sami as an object of oppression, and more recently they have presented the Sami as acting subjects in history. The question is not if, and to what extent, the Sami ought to be included in histories of Norway, but rather in what view the majority presents the indigenous people in the textbooks, for example. This discussion is relevant to debates on multiculturality in general and it also offers a deeper understanding of how history works in (ethno)political contexts.